Gut microbiota characterisation in obese patients before and after bariatric surgery. - Campisciano, G; Palmisano, S; Cason, C; Giuricin, M; Silvestri, M; Guerra, M; Macor, D; De Manzini, N; Crocé, L S; Comar, M (Benef Microbes, 2018)
Intestinal microbiota analysis of obese patients after bariatric surgery showed that Proteobacteria decreased after laparoscopic sleeve gastrectomy (SG), while it increased after laparoscopic gastric bypass (LGB). Comparing to normal weight (NW) patients, obese patients that were selected for SG showed an almost equal amount of Firmicutes and Bacteroidetes and the ratio was not affected by the surgery. Obese patients before LGB showed a predominance of Bacteroidetes, whose amount regained a relative abundance similar to NW patients after surgery. Obese patients before LGB showed the predominance of Bacteroides, which decreased after surgery in favour of Prevotella, a bacterium associated with a healthy diet. The bacteria detected at the highest percentages belonged to biofilm forming species. In conclusion, in this study, we found that the characterization of the gut microbial communities and the modality of mucosal colonisation have a central role as markers for the clinical management of obesity and promote the maintenance of good health and the weight loss.
Keywords: Adult; Bariatric Surgery; Gastrointestinal Microbiome; Humans; Laparoscopy; Microbiota; Middle Aged; Obesity; Young Adult